IMPACT OF TELEWORKING ON THE ADMINISTRATION OF THE HUMAN TALENTS DEPARTMENT - Enrique Cáceres Villalba, Derlis; Arnaldo González Villamayor, Hugo; del Mar Duarte Vallejo, María; Cañete Britez, Walter; Arnaldo Dávalos Giménez, Luís (Revista Gênero e Interdisciplinaridade, 2022)
The research presented aims to: Analyze the impact regarding the implementation of teleworking in the administration of human talents in Ciudad del Este, Republic of Paraguay. The research has a quantitative approach, the level of research is descriptive. The population is taken as 100 people from the different locations of Ciudad del Este, Alto Paraná, Paraguay, mentioned in the study, selecting 100% of the population for the sample, contacting them through social networks and consequently use a survey through the Google drive application to collect the data required for the investigation, using a semi-structured questionnaire as an instrument, from the result of which it is concluded that there is a high level of acceptance of the implementation of teleworking on the part of the respondents about of teleworking in the administration of the human talent department.